Musculoskeletal pain and physical health status among confirmed COVID-19 patients of Bangladesh (Bangabandhu Sheikh Mujib Medical University Journal, 2021)
COVID-19 pandemic is now a great headache for the world population. Respiratory symptoms are the main presentation of COVID-19. However, musculoskeletal pain, headache, loss of taste and smell sense, and neurological manifestations may occur. Identification of patterns of musculoskeletal pain, fatigue and physical health status in COVID-19 is crucial. In this cross sectional study, a total 380 individuals with COVID-19 were recruited from the population following selection criteria. Pain varied widely in hip, neck, leg and calf muscles, back and spine, shoulder, arms and hand, and other parts of the body among the respondents. Inconstant, among respondents of younger age group (aged ≤50 year), 37.59% had moderate pain, 6.77% had severe pain, 13.91% had mild pain, and 41.17% had no pain. On the other hand, among older respondents (aged >50 year) 47.37% had moderate pain, 25.44% had severe pain, 13.15% had mild pain, and 14.03% had no pain. The differences between two groups was statistically significant (p